BALF and BLOOD NK- cells in different stages of pulmonary sarcoidosis - Manika , Katerina; Domvri, Kalliopi; Kyriazis , George; Kontakiotis , Theodoros; Papakosta , Despina (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background and objective: Data on natural killer (NK)- and natural killer T (NKT)- like cells in the immunopathogenesis of sarcoidosis remain limited. The aim was to assess NK- and NKT-like cells across different stages in bronchoalveolar lavage (BALF) versus peripheral blood (PB) in comparison to controls. Methods: Forty four patients (32 women and 12 men, mean age 46.6±14.4 years) with biopsy-proven sarcoidosis and 10 healthy individuals (6 women, 4 men mean age 52.6±19.1 years) were submitted to BALF. Total cells and cell differentials were counted, while CD45+, CD3+, CD4+, CD8+, CD19+, CD3-CD16/56 (NK cells) and CD3+CD16/56+ (NKT-like cells) were determined by dual flow cytometry in BALF and PB. Results: A significantly lower percentage of both NK and NKT-like cells was observed in BALF of controls and sarcoid patients (SP) compared to PB. Both BALF NK and NKT-cell counts were significantly higher in SP than in controls (NK: p=0.046, NKT-like: p=0.012) In addition BALF NK cell percentage differed among sarcoidosis stages (p=0.005). In PB NK-cell count was lower in sarcoidosis patients but the difference did not reach statistical significance. Also, in sarcoid patients’ BALF NK-cell percentage negatively correlated with lymphocyte percentage (r=-0.962, p<0.001). Conclusions: The increased count of BALF NK and NKT-like cells in sarcoidosis compared to controls along with the increase of NK cells with stage progression are in line with a growing number of investigations suggesting the involvement of NK- and NKT-like cells in the pathogenesis of sarcoidosis.